MEDB-30. Subclassification of Group 3/4 medulloblastoma as a potential prognostic biomarker to reduce the dose of craniospinal irradiation in patients with metastatic tumors: A Japanese Pediatric Molecular Neuro-Oncology Group study. (3rd June 2022) - Fukuoka, Kohei; Kurihara, Jun; Mori, Makiko; Arakawa, Yuki; Yoshioka, Ema; Shofuda, Tomoko; Matsushita, Yuko; Hibiya, Yuko; Honda, Satoko; Nakazawa, Atsuko; Kiyotani, Chikako; Kagawa, Naoki; et al.
Abstract: BACKGROUND: In patients with medulloblastoma, one of the most significant challenges is to reduce the dose of craniospinal irradiation (CSI) to minimize neurological sequelae in survivors. Molecular characterization of patients treated using lower-dose CSI rather than standard therapy is important for further reducing the treatment burden. METHODS: We conducted DNA methylation analysis using an Illumina Methylation EPIC array to investigate molecular prognostic markers in 38 patients with medulloblastoma who were registered in the Japan Pediatric Molecular Neuro-Oncology Group and were treated using lower-dose CSI rather than standard-dose radiation therapy. RESULTS: Among the patients, 23 were classified as having a "standard-risk" and 15 as having a "high-risk" according to the classic classification based on tumor resection rate and presence of metastasis, respectively. The median follow-up period was 71.5 months. The median CSI dose was 18 Gy in both groups, and 10 patients in the "high-risk" group received a CSI dose of 23.4 Gy or 24 Gy. Molecular subgrouping revealed the "standard-risk" cohort included 5 WNT, 2 SHH, and 16 Group 3/4 cases; all 15 patients in the "high-risk" cohort had Group 3/4 medulloblastoma. Among the patients with Group 3/4 medulloblastoma, 13 of the 16 "standard-risk" patients were subclassified as subtypes I, IV, VI, and VII, which were associated with a good prognosis according to the novel sub-subclassification among Group 3/4 medulloblastomas. However, only 6 of the 15 "high-risk" patients were included in the subtypes. The good prognostic subtype cases among "high-risk" cohort were all survived without recurrence, in contrast to a worse prognosis (5-year progression free survival=33.3%; p=0.01) of the other cases. CONCLUSION: Although these findings require validation in a larger cohort, the present findings suggest that the novel sub-subclassification of Group 3/4 medulloblastoma may be a promising prognostic biomarker for reducing the dose of CSI in patients with metastatic medulloblastoma.